Spatio-temporal overlap between the at-sea distribution of Southern Giant Petrels and fisheries at the Patagonian Shelf - Copello, Sofía; Quintana, Flavio Roberto (Polar Biology)
The interactions between seabirds and fisheries pose significant threats for the seabird species such as incidental capture. In contrast, several species of seabirds meet part of their energetic requirements through the use of fisheries discards. Knowledge about the relationship between at-sea distribution of Procellariiformes and fisheries is a key tool in marine ecosystem management. We analysed the spatio-temporal relationship between the areas used by 16 satellite-tracked breeding adults of the Southern Giant Petrel and fisheries distribution and catch at the Patagonian Shelf. We also determined the time spent by adults in different marine jurisdictions. Results indicated a marked spatio-temporal association between birds and fisheries, mainly trawlers. The Southern Giant Petrels concentrated their foraging effort over Argentinean waters. The use of an abundant and predictable food source provided by the fisheries discards may be one of the factors affecting the dynamics of the Southern Giant Petrel populations in Patagonia, Argentina. Fil: Copello, Sofía. Universidad Nacional de Mar del Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos